SYNCHRONOUS RECORD OF δ13C SHIFTS IN THE OCEANS AND ATMOSPHERE AT THE END OF THE PERMIAN - Sephton M.A.; Veefkind R.J.; De Leeuw J.W.; Looy C.V.; Brinkhuis H.; Visscher H. (My University, 2002)
In conjunction with the profound ecologic crisis at the end of the Permian, the most conspicuous geochemical event is the worldwide negative shift in the carbon isotopic composition (δ13C) of both carbonates and sedimentary organic matter. Comparative carbon isotopic analyses of carbonates and the molecular fossils of land plant leaf cuticles from a marine Permian-Triassic transition section in the southern Alps, northeastern Italy, substantiates the concept of synchronous disturbances in oceanic and atmospheric chemistry and, therefore, verifies the primary nature of the end-Permian δ13C disturbance. The δ13C excursion appears to be a consequence of the ecological crisis, and the global reservoir of soil organic matter may be the only plausible source of 13C-depleted carbon.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская